A N, P Dual‐Doped Carbon with High Porosity as an Advanced Metal‐Free Oxygen Reduction Catalyst. Issue 14 (5th June 2019) - Sun, Ya‐Nan; Zhang, Ming‐Li; Zhao, Li; Sui, Zhu‐Yin; Sun, Zhen‐Yu; Han, Bao‐Hang
Abstract: Oxygen reduction reaction (ORR) is the critical reaction in metal–air batteries and fuel cells. This reaction suffers from sluggish kinetics and use of Pt‐based catalysts that are prohibitively expensive and in shortage of resource. Therefore, an alternative advanced metal‐free catalyst for ORR is highly desired. Herein, a N, P dual‐doped porous carbon (NPPC) with large surface area is obtained through the CO2 activation of a novel N, P‐doped aerogel (NPA). Ascribed to the CO2 activation of NPA, NPPC possesses a large Brunauer–Emmett–Teller specific surface area (2850 m 2 g −1 ) and N, P dual doping. CO2 activation as an environmentally friendly method with no corrosion can not only produce abundant micropores and mesopores in NPPC, but also provide a positive influence for the transformation of N species from pyrrolic N to pyridinic and graphitic N, which can promote the ORR activities. Therefore, compared with carbonized NPA, NPPC exhibits a higher ORR activity, including a larger transfer electron number (3.95 at 0.2 V vs reversible hydrogen electrode). Additionally, NPPC possesses a much better long‐term stability compared with commercial 20 wt% Pt/C. This work gives an inspiration on the new strategy for preparing the future catalyst for ORR. Abstract : N, P dual‐doped porous carbon (NPPC) with high Brunauer–Emmett–Teller surface area (2850 m 2 g −1 ) is prepared through the CO2 activation of a novel N, P‐doped aerogel. When used as a metal‐free oxygen reduction reaction (ORR) catalyst, NPPC possesses a high ORR activity and an excellent stability.